PWE-032 Golimumab in ulcerative colitis: a multi-centre real world experience. (8th June 2018) - Kumar, Aditi; Slater, Jayne; Jones, Judith; Troth, Tom; Baker, Graham; Love, Melanie; Nihal, Jasbir; Rattehalli, Deepa
Abstract : Introduction: Golimumab (Simponi) is a TNFα inhibitor approved for patients with ulcerative colitis (UC) since 2013. Pre-clinical work showed superiority to both infliximab and adalimumab in mechanism of action. Initial trial data showed 51% achieved clinical remission by week 6% and 47% by week 54. However there is no real world data to correlate these findings. We aimed to assess the effectiveness of golimumab in a real world setting. Methods: A retrospective multicentre study was conducted between 2014 to date. Data was obtained from 5 hospitals around the West Midlands, UK. Inclusion criteria included patients with a diagnosis of moderate to severe ulcerative colitis (endoscopic Mayo score ≥2.) Dosing was weight dependent (≤80 kg=50 mg 4-weekly;≥80 kg=100 mg 4-weekly following an induction dose). Data was collected using patient notes and endoscopy reports. Fisher's exact test was used for statistical significance. Results: There were a total of 56 patients with a mean age of 39.2 years (M=39; F=17). The majority of patients had left sided disease (48%; n=27) followed by pancolitis (45%; n=25) and proctitis (7%; n=4). 64% were on concurrent immunosuppressants. The mean duration of golimumab treatment was 12 months. One patient developed deranged liver function tests on golimumab. They were switched to vedolizumab. Twenty-two patients (39%) showed endoscopic and clinical remission (proctitis n=3; left sided n=9; pancolitis n=10). There was no statistically significant difference between disease extent and remission (p=1.00). Of these 22 patients, 17 patients were on the higher dose of 100 mg, with a statistical significance between the dosing (p=0.03). Three patients who were initially on 50 mg and relapsed had their dose increased to 100 mg. They remain in remission. Of the 50% (n=28) who switched biologic therapy, 23 were to vedolizumab, 1 to infliximab and 4 to adalimumab. Despite changing to vedolizumab, 3 (13%) patients still required surgery. Patients switched to adalimumab and infliximab are currently in remission. In total, 14% (n=8) required surgery, of which 3 patients had emergency surgery. Conclusion: Golimumab has not proven as effective in our real world data. Two important inferences were made from this study. Firstly, of those patients that went into remission, 75% were on the higher dose of golimumab. This may be secondary to higher trough levels; however therapeutic drug monitoring is currently unavailable in the UK for golimumab. Secondly, 5 patients who were switched to an alternative anti-TNF, where drug monitoring is available, had a good clinical response. This leads us to propose that drug-monitoring is of clinical importance and should be available for golimumab in the UK to help maintain clinical remission.